Impact of daratumumab on stem cell mobilization and transplant in patient with newly diagnosed multiple myeloma: a real word single-center study - Mauro Passucci; Francesca Fazio; Jacopo Micozzi; Manhaz Shafii Bafti; Giovanni Manfredi Assanto; Alfonso Piciocchi; Maurizio Martelli; Maria Teresa Petrucci (Mediterranean Journal of Hematology and Infectious Diseases)
Not applicable.